2016
DOI: 10.3892/etm.2016.3674
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA pretreatment attenuates ischemia/reperfusion-induced renal injury

Abstract: Abstract. Tanshinone IIA is a chemical compound extracted from the root of traditional Chinese herb Salvia miltiorrhiza Bunge. Tanshinone IIA has been suggested to possess anti-inflammatory activity and antioxidizing capability. Recently, accumulating results have indicated the antitumor activity of tanshinone IIA; thus, it has attracted increasing attention. In addition, tanshinone IIA has been indicated to attenuate ischemia/reperfusion induced renal injury (I/RIRI); however, little is known regarding the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…A recent study reported that Tanshinone IIA could up-regulate the expression of Bcl-2, an anti-apoptotic protein [10]. On another hand, it was also reported Nrf2 activation contributed to Tanshinone IIA induced neuroprotection by inducing transcription of large numbers of antioxidant genes including heme oxygenase-1 (HO-1) [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that Tanshinone IIA could up-regulate the expression of Bcl-2, an anti-apoptotic protein [10]. On another hand, it was also reported Nrf2 activation contributed to Tanshinone IIA induced neuroprotection by inducing transcription of large numbers of antioxidant genes including heme oxygenase-1 (HO-1) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone IIA is an active monomer extracted from S. miltiorrhiza [8], which plays a key role in the plant’s clinical efficacy. Previous studies suggest that Tanshinone IIA is neuroprotective in cerebral ischemia reperfusion injury [8, 9] and renoprotective in renal ischemia reperfusion injury [10]. .…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, some anti-in ammatory agents have been discovered, including αmelanocyte stimulating hormone, anti-apoptotic agents, and IL-6 inhibitors [38,39]. A previous study reported that renal IR induces dysfunction in lung mitochondria and dexmedetomidine attenuates lung in ammation, apoptosis, and the MMP [38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intensive research has discovered the renoprotective effect of STS, which has drawn much significant attention and is becoming a research hot spot. Recent publications have demonstrated that tanshinone IIA can exert its renoprotective effects by fighting oxidative stress, attenuating renal fibrosis, regulating inflammation, counteracting ischemia-reperfusion injury, protecting podocytes and endothelial cells, and ameliorating microcirculatory disturbance (Han et al, 2008;Wang et al, 2015;Xu et al, 2016;Cao et al, 2017;Zhu et al, 2017). Increasing evidence indicates that STS combined with antihypertensive drugs like ARBs can additively alleviate the renal dysfunction induced by hypertension.…”
Section: Discussionmentioning
confidence: 99%